Supervisory Board Qualification of German Banks - Legal Standards and Survey Evidence - Tobias Körner; Oliver Müller; Stephan Paul; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
Improving the regulation of banks has been at the centre of economic policy actions since the outbreak of the global financial crisis. One of the many and conceptually very different measures proposed is to improve the corporate governance of banks by setting qualification standards for banks' non-executive directors. To explore the rationale of such a regulation implemented in Germany, we conducted a detailed survey among supervisory board members of German banks covering their educational background, professional status and experience, as well as non-occupation related activities. We document that general education among supervisory board members is high, but very few board members can rely on a professional background in banking and finance. Surprisingly, we find that this is especially true for chairpersons and that a higher share of professionals among board members primarily reflects the presence of employee representatives. However, as regards competencies and skills required to enforce changes against the management, chairpersons more often report leadership experience than ordinary members. Furthermore, some of these fi ndings strongly depend on the bank's legal form, its size and business model, suggesting that both market forces and institutional characteristics of banking markets are important determinants of the qualification level of non-executive directors. – – Seit Ausbruch der globalen Finanzkrise steht das Thema Bankenregulierung ganz oben auf der wirtschaftspolitischen Agenda. Die Reformansätze sind vielfältig und unterscheiden sich konzeptionell zum Teil sehr deutlich. Eine Gruppe von Vorschlägen zielt auf die Verbesserung der internen Corporate Governance von Kreditinstituten ab, beispielsweise durch bankaufsichtliche Vorgaben an die Qualifikation ihrer Kontrollorganmitglieder. Der vorliegende Beitrag hinterfragt diesen in Deutschland bereits im Jahr 2009 implementierten Ansatz auf Basis einer detaillierten Befragung, unter anderem zu Ausbildung, beruflichem Hintergrund und nebenberuflichen Tätigkeiten von Kontrollorganmitgliedern. Die Befragungsergebnisse zeigen, dass Kontrollorganmitglieder im Mittel über einen hohen Bildungsstand verfügen. Sie haben jedoch nur recht selten berufliche Erfahrung in der Finanzindustrie. Insbesondere gilt dies für die Vorsitzenden der Kontrollorgane. Der beobachtete höhere Anteil an Kontrollorganmitgliedern mit Berufserfahrung in der Finanzindustrie bei öffentlich-rechtlichen Sparkassen und Aktiengesellschaften spiegelt die verstärkte Präsenz von Arbeitnehmervertretern wider. Mehrheitlich verfügen Kontrollorganmitglieder über Führungserfahrung, besonders häufig können Vorsitzende darauf verweisen. Viele der erhobenen Qualifikationsmerkmale variieren stark mit Rechtsform, Größe und Geschäftsmodell des beaufsichtigten Instituts. Marktkräfte und institutionelle Charakteristika des deutschen Bankensektors sind demnach wichtige Bestimmungsfaktoren für das Qualifikationsniveau von Kontrollorganmitgliedern.
Keywords: G21; G28; G34; 330; non-executive directors; qualification; survey data; banking regulation; German banking system